The frozen elephant trunk technique: impact of proximalization and the four-sites perfusion technique - Tsagakis, Konstantinos; Osswald, Anja; Weymann, Alexander; Demircioglu, Aydin; Schmack, Bastian; Wendt, Daniel; Jakob, Heinz; Ruhparwar, Arjang (European journal of cardio-thoracic surgery, 2021)
Abstract